Keterkaitan Kinerja Pemasaran dan Orientasi Pelanggan, Orientasi Kewirausahaan, Sistem Reward dan Orientasi Pembelajaran Sebagai Variabel Anteseden - darmanto - anto; Yusup Hari Subagya (Media Akuntansi, 2015)
This research is intended to provide information about conceptual controversy relevant to the role of anteseden variable customer orientation on marketing performance. In particular, it is to provide information about the influence of entrepreneurship, marketing-based reward and learning orientation on the customer orientation, the influence of customer orientation on the marketing performance. Scientifically, this research gives contributions in explaining factors that affect the orientation of customer for SMEs in food sector; and giving suggestion to the government in its efforts to develop SMEs in food sector. Population of this research were owners or managers of SMEs in food sector in Boyolali, Surakarta, Sukoharjo, Karanganyar, Wonogiri, Sragen and Klaten. The research used sampling convenience method, and the number of sample was 250. The method applied in analyzing the data was the Structural Equation Modeling with Lisrel software. This research reveals the results: Orientation of entrepreneurship, marketing-based reward and learning bring positive and significant effect on customer orientation, orientation customer have positive and significant influence on marketing performance.